Analisis Kemampuan Literasi Digital Mahasiswa Universitas Merdeka Malang dalam Menggunakan Aplikasi Unmer Malang Digital Library - Aqilah Dzira Afiyani; Annisa Fajriyah; Nita Siti Mudawamah; Anindya Gita Puspita (UIN Maulana Malik Ibrahim Malang, 2026)
The UNMER Malang Digital Library application was released in December 2023 through a cooperation agreement with PT. Woolu Aksara Maya. A socialization event related to the use of the application was held once during the release of the application, which was only attended by representatives of several students from Universitas Merdeka Malang, so that information related to the use of the application was not received equally by all students. This resulted in a low number of app downloads, users, and accesses. Additionally, students faced challenges in determining keywords to search for e-books. This study aims to measure the level of digital literacy among students at Universitas Merdeka Malang in using the UNMER Malang Digital Library app. The population for this study consisted of 491 users of the UNMER Malang Digital Library application. A sample was then selected using non-probability sampling with the Slovin formula, resulting in 83 respondents. The method used was descriptive quantitative, meaning that the percentage of each research indicator was calculated and then analyzeddescriptively. The results of this study indicate that the level of digital literacy among students at Universitas Merdeka Malang in using the UNMER Malang Digital Library application falls within the high category, with a grand mean score of 3.64 when measured across the 10 indicators used. These indicators include accessing, understanding, analyzing, verifying, evaluating, distributing, producing, participating, and collaborating. This means that, fundamentally, students at Universitas Merdeka Malang already possess good accessing skills for the application. They are also able to filter the information they need, ensure the accuracy of the information obtained, and organize it into another form accurately, clearly, and easily understood. The ability to collaborate with others in sharing information is also possessed by students at Universitas Merdeka Malang.